The Effects of Soft Tissue Flossing on Hamstring Range of Motion and Lower Extremity Power - Zachary Maust; Debbie Bradney; Sean M Collins; Caroline Wesley; Thomas G Bowman (International Journal of Sports Physical Therapy)
# Background